Electrical conductivity of the seed soaking solution and soybean seedling emergence - Vieira, Roberval Daiton [UNESP]; Neto, A. S.; de Bittencourt, SRM; Panobianco, M. (Universidade de São Paulo (USP), 2004)
Vigor of soybean [Glycine max (L.) Merrill] seeds can be evaluated by measuring the electrical conductivity (EC) of the seed soaking solution, which has shown a satisfactory relationship with field seedling emergence, but has not had aproper definition of range yet. This work studies the relationship between EC and soybean seedling emergence both in the field and laboratory conditions, using twenty two seed lots. Seed water content, standard germination and vigor (EC, accelerated aging and cold tests) were evaluated under laboratory conditions using -0.03; -0.20; -0.40 and -0.60 MPa matric potentials, and field seedling emergence was also observed. There was direct relationship between EC and field seedling emergence (FE). Under laboratory conditions, a decreasing relationship was found between EC and FE as water content in the substrate decreased, Relationships between these two parameters were also found when -0.03; -0.20 and -0.40 MPa matric potentials were used. EC tests can be used successfully to evaluate soybean seed vigor and identify lots with higher or lower field emergence potential.
Keywords: Glycine max; Vigor; physiological quality; water stress